P718A novel TGF beta-dependent signalling pathway regulating vascular smooth muscle cell differentiation. (15th July 2014) - Pagiatakis, C; Sun, D; Wales, S; Mcdermott, JC
Abstract: Purpose: Vascular smooth muscle cells (VSMCs) do not terminally differentiate; they fluctuate between a proliferative and differentiated state in response to various extracellular signals. This phenotypic modulation is a major factor that contributes to vascular diseases such as atherosclerosis and post-angioplasty restenosis. Thus, the mechanisms regulating VSMC phenotype are of great interest. TGFβ has been implicated in inducing VSMC differentiation via RhoA/ROCK signalling, whereby it induces a contractile phenotype in neural crest stem cells by up-regulating smooth muscle structural genes. Previous work in our lab showed that RhoA is involved in regulating contractile genes via regulation of myocardin expression. Therefore, we hypothesized that TGFβ is involved in regulating smooth muscle cell differentiation via downstream targets of RhoA/ROCK and components of the canonical TGFβ pathway. Methods: We utilized primary VSMCs and mouse embryonic fibroblast cells (10T1/2) in a conversion assay where cells were induced to express VSMC genes. We utilized siRNA to knock down gene expression, along with gene transfection techniques, reporter assays and pharmacological inhibitors. Results: Treatment of 10T1/2 cells with TGFβ results in a potent induction of VSMC marker genes at the transcriptional and protein levels, which is attenuated by inhibition of RhoA/ROCK signalling. Since canonical TGFβ signalling induces formation of Smad protein complexes which regulate gene expression of numerous target genes, a possible effector could be a downstream component of TGFβ signalling, TAZ, a potent transcriptional regulator and nuclear retention factor that is recruited to sites of Smad-mediated transcription in a TGFβ-dependent manner. Our studies show that in 10T1/2 cells, TAZ is required for TGFβ induction of smooth muscle marker genes. Interestingly, these observations appear to be ROCK dependent. Furthermore, we have observed a synergistic effect between TAZ and Smad3 in regulating smooth muscle differentiation, an effect which is enhanced by serum response factor (SRF). Interestingly, SRF is also required for the TGFβ induction of smooth muscle markers in 10T1/2 cells. Conclusions: These data provide evidence of a novel signalling pathway that links RhoA/ROCK-dependent TGFβ signalling to induction of smooth muscle genes in embryonic fibroblasts through a mechanism involving regulation and expression of TAZ and SRF proteins. These observations elucidate a novel level of control of VSMC induction which may have implications for vascular diseases and congenital vascular malformations.